Comparison of Graft Uptake in Perforated Eardrums with and without Myringosclerosis: A Prospective Case-control Study in a Tertiary Centre - Rehman, Ayaz; Deva, Faizah Ashfah Latief; Wani, Asef Ahmad; Masoodi, Majid; Malik, Bashir; Makhdoomi, Owais (International Archives of Otorhinolaryngology, 2025)
Introduction Various factors have been reported to affect the rates of success after tympanoplasty, among them, myringosclerosis. However, there are few studies focusing only on the effect of myringosclerotic plaque removal on tympanoplasty outcomes.Objective To compare the outcome of tympanoplasty in perforated eardrums with and without myringosclerosis.Methods The study included patients aged between 21 and 53 years diagnosed at the outpatient department with inactive mucosal chronic otitis media. The sample was divided into the case group, which included subjects with tympanic membrane perforation and myringosclerosis, and the control group, which included subjects with tympanic membrane perforation only, without myringosclerosis. We assessed the audiological findings of the patients before and after surgery, as well as hearing gain, graft uptake, and residual perforation/reperforation.Results No significant relationships were observed involving the age or sex of the patient and the closure rate or hearing gain, neither between the location of the perforation and graft uptake. Graft uptake was higher in patients with perforation size < 50%. The graft uptake and hearing gain were higher in the case group.Conclusion The removal of sclerotic plaques increases the surface of the raw area created by subepithelial excision of the myringosclerotic plaques, leading to a high rate of surgical success for the closure of tympanic membrane defects with coexisting myringosclerosis.
Keywords: otitis media; tympanic membrane perforation; sclerosis; tympanoplasty; uptake; outcome